Rapid Ventricular Pacing as a Safe Procedure for Clipping of Complex Ruptured and Unruptured Intracranial Aneurysms - Josefin Grabert (MDPI AG, 2021)
Surgical treatment of intracranial aneurysm requires advanced technologies to achieve optimal results. Recently, rapid ventricular pacing (RVP) has been described to be an elegant technique that facilitates clip reconstruction of complex unruptured intracranial aneurysm (uIA). However, there is also a growing need for intraoperative tools to ensure safe clip reconstruction of complex ruptured intracranial aneurysm (rIA). We conducted a retrospective analysis of 17 patients who underwent RVP during surgical reconstruction of complex aneurysms. Nine patients had uIA while eight patients underwent surgery for rIA suffering from consecutive subarachnoid hemorrhage (SAH). Hemodynamic data, critical events, laboratory results, and anesthesia-related complications were evaluated. No complications were reported concerning anesthesia induction and induction times were similar between patients exhibiting uIA or rIA (p = 0.08). RVP induced a significant decline of median arterial pressure (MAP) in both groups (p < 0.0001). However, median MAP before and after RVP was not different in both groups (uIA group: p = 0.27; rIA group: p = 0.18). Furthermore, high-sensitive Troponin T (hsTnT) levels were not increased after RVP in any group. One patient in the rIA group exhibited ventricular fibrillation and required cardiopulmonary resuscitation, but has presented with cardiac arrest due to SAH. Otherwise, no arrhythmias or complications occurred. In summary, our data suggest RVP to be feasible in surgery for ruptured intracranial aneurysms.